2014
DOI: 10.1007/s11432-014-5146-0
|View full text |Cite
|
Sign up to set email alerts
|

Fuzziness parameter selection in fuzzy c-means: The perspective of cluster validation

Abstract: Intelligent diagnosis of the solder bumps defects using fuzzy C-means algorithm with the weighted coefficients SCIENCE CHINA Technological Sciences 58, 1689 (2015); Defect inspection of flip chip package using SAM technology and fuzzy C-means algorithm SCIENCE CHINA Technological Sciences 61, 1426 (2018); Land cover classification of remote sensing imagery based on interval-valued data fuzzy c-means algorithm SCIENCE CHINA Earth Sciences 57, 1306 (2014);. RESEARCH PAPER. SCIENCE CHINA Information Sciences

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…We ran the FA for different values of m in order to find the optimal parameter of fuzziness and chose the one that gives the best results. Recently, Zhou et al reported that the optimal interval of the parameter m is from 2 to 3.5. In our study, we range the parameter m from 1.5 to 3.5 with increments of 0.5. Shape of membership functions: Many shapes of membership functions can be used such as triangular, trapezoidal, and Gaussian. Number of fuzzy clusters: for a real dataset, the number of clusters, k , is usually unknown in advance.…”
Section: Empirical Designmentioning
confidence: 99%
See 1 more Smart Citation
“…We ran the FA for different values of m in order to find the optimal parameter of fuzziness and chose the one that gives the best results. Recently, Zhou et al reported that the optimal interval of the parameter m is from 2 to 3.5. In our study, we range the parameter m from 1.5 to 3.5 with increments of 0.5. Shape of membership functions: Many shapes of membership functions can be used such as triangular, trapezoidal, and Gaussian. Number of fuzzy clusters: for a real dataset, the number of clusters, k , is usually unknown in advance.…”
Section: Empirical Designmentioning
confidence: 99%
“…We ran the FA for different values of m in order to find the optimal parameter of fuzziness and chose the one that gives the best results. Recently, Zhou et al 45 reported that the optimal interval of the parameter m is from 2 to 3.5. In our study, we range the parameter m from 1.5 to 3.5 with increments of 0.5.…”
Section: Case Adaptationmentioning
confidence: 99%
“…To discovery valuable knowledge and fully realize the business potential of energy big data, various big data analytics techniques, such as data quality evaluation and modeling [103][104][105], data clustering and classification [68,[106][107][108][109], stream data processing [110][111][112], knowledge inference [113,114], statistical machine learning [115], neural networks modeling and deep learning [116,117], can be implemented on the data. The objective of energy big data analytics is to develop more effective and efficient data-driven applications and services.…”
Section: Energy Big Data Driven Applications In Energy Internetmentioning
confidence: 99%
“…However, there is no recommended value of m . Zhou et al reported that the optimal interval of the m parameter is from 2 to 3.5. In this study, we ranged m from 1.5 to 3.5 in increments of 0.1. Number of fuzzy clusters: The number of clusters was varied within the interval for all features in each dataset.…”
Section: Empirical Designmentioning
confidence: 99%
“…• Parameter of fuzziness (m): Prior studies on FCM reported that the result of clustering is significantly affected by the variation of parameter m. 86,87 However, there is no recommended value of m. Zhou et al 88 reported that the optimal interval of the m parameter is from 2 to 3.5.…”
Section: Configuration Of Filters and Single Fuzzy Analogy Techniquesmentioning
confidence: 99%